Levels and diagnostic value of model-based insulin sensitivity in sepsis: a preliminary study - Wan Fadzlina, Muhd Shukeri; Mohd Basri, Mat Nor; Ummu Kulthum, Jamaludin; Fatanah, M. Suhaimi; Normy Norfiza, A. Razak; Azrina, Md Ralib (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: Currently, there is a lack of real‑time metric with high sensitivity and specificity to diagnose sepsis. Insulin sensitivity (SI) may be determined in real‑time using mathematical glucose‑insulin models; however, its effectiveness as a diagnostic test of sepsis is unknown. Our aims were to determine the levels and diagnostic value of model‑based SI for identification of sepsis in critically ill patients. Materials and Methods: In this retrospective, cohort study, we analyzed SI levels in septic (n = 18) and nonseptic (n = 20) patients at 1 (baseline), 4, 8, 12, 16, 20, and 24 h of their Intensive Care Unit admission. Patients with diabetes mellitus Type I or Type II were excluded from the study. The SI levels were derived by fitting the blood glucose levels, insulin infusion and glucose input rates into the Intensive Control of Insulin‑Nutrition‑Glucose model. Results: The median SI levels were significantly lower in the sepsis than in the nonsepsis at all follow‑up time points. The areas under the receiver operating characteristic curve of the model‑based SI at baseline for discriminating sepsis from nonsepsis was 0.814 (95% confidence interval, 0.675–0.953). The optimal cutoff point of the SI test was 1.573 × 10−4 L/mu/min. At this cutoff point, the sensitivity was 77.8%, specificity was 75%, positive predictive value was 73.7%, and negative predictive value was 78.9%. Conclusions: Model‑based SI ruled in and ruled out sepsis with fairly high sensitivity and specificity in our critically ill nondiabetic patients. These findings can be used as a foundation for further, prospective investigation in this area.